Draft Annual Plan 1993-94 Volume-I (Memorandum along with Statements) Haryana Government - Planning Commission (Planning Commission, 1992)
The Planning Commission, Govt. of India have listed the following objectives/priority areas to be pursued during the Eighth Plan :— employment generation; containment of population growth: universalisation of elementary education, complete eradication of illiteracy among people of the age group of 15 to 35 years; eradication of scavenging a and provision of safe di inking water, health care and immunisation to all villages, growth and diversification of agriculture to achieve self sufficiency in food and generation of surplus for export; strengthening of infrastructure facilities i.e. energy, transport, communication and irrigation in older to support the processor growth in a sustainable manner; and effective decentralisation, encouragement official initiatives, voluntary efforts, etc.
Planning Department, Government of Haryana